TEACHING ENGLISH VOCABULARY THROUGH THINK TALK WRITE METHOD - Yahya Amalia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
The research focused on the use of think talk write method developing students’ English vocabulary at the eighth year students  SMP Datuk Sulaeman Putri Palopo. The research problem is that: does think talk write method effectively develop students’ vocabulary at the students of SMP Datuk Sulaeman Putri Palopo? . The population of this research is the eighth year students of SMP Datuk Sulaeman Putri Palopo. consists of 120 students. In this research, the researcher used vocabulary test to assess and examine the students’ writing vocabulary. The test are pre-test and post-test. The researcher collected data by using vocabulary test.  The result of this research shows that there is significant development on students’ vocabulary at the eighth year students of SMP Datuk Sulaeman Putri Palopo after conducting the treatment by using think talk write method. In which of tcount (26.544) is bigger than the score of ttable (2.048). it means that think talk write method gives significant contribution towards students’ vocabulary development.